(untitled) (London Journal of Medical and Health Research, 2024)
Feelings play an increasingly important role in psychoanalysis and neuroscience. Following some general reflections, we introduce the concept of predictive coding or anticipatory simulation. Within this framework, feelings are constructed judgements on inner simulative states. Both feelings and language have the task of investing inner states with meaning and rendering this meaning communicable. Feelings are conscious; they constitute the first form of phenomenal consciousness. This scientific approach can easily be formulated as part of the Lacanian metapsychology. We will show, that the linking of both perspectives enables a gain of knowledge. Thus, for instance, the Marko blanket can be understood as a function of the Real, and the theory of predictive coding sheds light on the characteristics of the Imaginary. Phenomena such as transference, countertransference or projective identification can also be better elaborated against this interdisciplinary backdrop.